Banks’ capital, regulation and the financial crisis - Teixeira, João (2019)
This paper investigates whether regulatory capital requirements play an important role in determining banks’ equity capital. We estimate equity capital regressions using panel data of a sample of 560 banks for 2004-2010. Our results suggest that regulatory capital requirements are not first order determinants of banks’ capital structure. We document differences on the effect of most factors on banks’ share of equity according to the type of bank and to the region of the bank. Finally, we show that the determinants of this share are sensitive to the recent international financial crisis and to a set of regulatory country factors.